Chronic Alcoholism Decreases Polyunsaturated Fatty Acid Levels in Human Plasma, Erythrocytes, and Platelets – Influence of Chronic Liver Disease - Pita, María-Luisa; Rubio, José-María; Murillo, María-Luisa; Carreras, Olimpia; Delgado, Mariá-José (Thrombosis and Haemostasis, 1997)
The effect of chronic ethanol ingestion on fatty acid composition of plasma, erythrocyte and platelet phospholipids and on plasma 6-keto-PGF1α was studied. Two groups of alcoholic subjects, one of them with chronic liver disease, were studied and compared to a control group of healthy subjects. Linoleic acid was not affected by alcoholism but its larger metabolites arachidonic acid (20:4n6) and docosatetraenoic acid (22: 4n6) tended to be lower in erythrocytes and platelets of both groups of alcoholic patients; the decrease was more marked in the presence of chronic liver disease. Docosahexaenoic acid (22:6n3) was markedly decreased in plasma, erythrocytes and platelets obtained from alcoholic patients with chronic liver disease. Plasma levels of 6-keto-PGF1α, a metabolite of prostacyclin (PGI2), remained unchanged. We conclude that chronic ethanol ingestion induces important changes in long-chain polyunsaturated fatty acids, mainly in platelets, and that these changes are exacerbated when patients suffer from chronic liver disease.